2003
DOI: 10.1007/s00442-002-1075-5
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO 2 lowers relative and absolute herbivore density across all species of a scrub-oak forest

Abstract: The unabated increase in global atmospheric CO(2) is expected to induce physiological changes in plants, including reduced foliar nitrogen, which are likely to affect herbivore densities. This study employs a field-based CO(2 )enrichment experiment at Kennedy Space Center, Florida, to examine plant-herbivore (insect) interactions inside eight open-topped chambers with elevated CO(2) (710 ppm) and eight control chambers with ambient CO(2). In elevated CO(2) we found decreased herbivore densities per 100 leaves,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 30 publications
6
66
2
Order By: Relevance
“…Plants respond to elevated CO 2 through changes in leaf chemistry, which reduce tissue nutritional quality for herbivores. This affects herbivore feeding behavior, development time and predation risk [25], leading to larger effects on community dynamics [26].…”
Section: Reviewmentioning
confidence: 99%
“…Plants respond to elevated CO 2 through changes in leaf chemistry, which reduce tissue nutritional quality for herbivores. This affects herbivore feeding behavior, development time and predation risk [25], leading to larger effects on community dynamics [26].…”
Section: Reviewmentioning
confidence: 99%
“…It was previously suggested that herbivores would respond to altered plant primary and secondary metabolism under elevated CO 2 by increasing food consumption to compensate for the plant lowered nutritional quality (e.g., Fajer 1989, Marks & Lincoln 1996, by reducing their growth rates and prolonging their development time (e.g., Smith & Jones 1998, Goverde & Erhardt 2003, and by reducing food conversion ef iciency (e.g., Lawler et al 1997, Brooks & Whittaker 1998. These reductions in herbivore performance under CO 2 enrichment would have the potential to increase mortality imposed by natural enemies (e.g., Fajer 1989, Stiling et al 2003, ultimately reducing herbivore abundance, richness and diversity if compared to ambient CO 2 conditions (Fig 1).…”
Section: Eff Ects Of Elevated Co 2 On Plant Chemistry and Herbivore Pmentioning
confidence: 99%
“…It was previously suggested that herbivores would respond to altered plant primary and secondary metabolism under elevated CO 2 by increasing food consumption to compensate for the plant lowered nutritional quality (e.g., Fajer 1989, Marks & Lincoln 1996, by reducing their growth rates and prolonging their development time (e.g., Smith & Jones 1998, Goverde & Erhardt 2003, and by reducing food conversion ef iciency (e.g., Lawler et al 1997, Brooks & Whittaker 1998. These reductions in herbivore performance under CO 2 enrichment would have the potential to increase mortality imposed by natural enemies (e.g., Fajer 1989, Stiling et al 2003, ultimately reducing herbivore abundance, richness and diversity if compared to ambient CO 2 conditions (Fig 1).But, by how much are insects affected by elevated CO 2 conditions? In general, the results of the meta-analysis of Stiling & Cornelissen (2007) demonstrated strong responses of herbivores to elevated CO 2 conditions, such as 1) a decline in insect abundance of almost 22.0% in elevated as compared to ambient CO 2 conditions, 2) an increase of almost 17.0% in consumption rates, 3) an increase of almost 4.0% in development time, 4) a decrease of 9.0% in relative growth rate and of 5) 5.0% in pupal weight.…”
mentioning
confidence: 99%
“…Plants grown under elevated CO2 had decreased leaf foliar nitrogen concentrations and increased C:N ratios; there was less damage from herbivores on these lower quality leaves (Stiling et al 2003, Hall et al 2005. Few legacy effects of elevated CO2 were found to persist one year after exposure to elevated CO2 concentrations was terminated; no differences remained in leaf nitrogen concentration or in herbivore densities ).…”
Section: Plant Physiology -Case Studymentioning
confidence: 96%